THE IMPACT OF CAR, CREDIT RISK, ROA, LDR, AND OWNERSHIP STRUCTURE TOWARDS FINANCIAL DISTRESS - Margaretha, Jennifer; Wijaya, Henryanto (International Journal of Application on Economics and Business, 2023)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Credit Risk, Return on Assets (ROA), Loan-to-Deposit Ratio (LDR), Institutional Ownership and Managerial Ownership on Financial Distress in the conventional commercial banking sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2020. This study used 15 conventional commercial banks as samples, which were then analyzed with multiple linear regression analysis techniques and panel data models. The results of this study show that CAR, ROA, and LDR have a positive and significant effect on Financial Distress; Credit Risk and Institutional Ownership have a negative and insignificant effect on Financial Distress; and Managerial Ownership has a positive and insignificant effect on Financial Distress. Other results, namely CAR, Credit Risk, ROA, LDR, Institutional Ownership, and Managerial Ownership simultaneously have a significant influence on Financial Distress.